2015
DOI: 10.1091/mbc.e14-07-1248
|View full text |Cite
|
Sign up to set email alerts
|

Centrin 3 is an inhibitor of centrosomal Mps1 and antagonizes centrin 2 function

Abstract: Cetn3 inhibits Mps1 kinase activity in vitro and at centrosomes by blocking activating autophosphorylation and can prevent Mps1 from phosphorylating Cetn2 even when Mps1 is present at 10-fold molar excess. Cetn3 also prevents incorporation of Cetn2 into centrioles, but mimicking phosphorylation of Cetn2 bypasses the inhibitory effects of Cetn3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Given that the Ca 2+ binding proteins calmodulin (22) and centrin-2 (49) are required for mitosis, this work now provides the missing link that connects the cell biology of Ca 2+ signaling with mitosis in mammalian cells and has important implications for furthering our understanding of normal growth, development, and ageing. Because centrins-2 and -3 are centrosome-associated Ca 2+ binding proteins (50), this could be a clue as to why a centrosome-localized Ca 2+ signal is of crucial importance. Centrosomally localized Ca 2+ signaling is likely a universal phenomenon essential during mitosis and represents an entirely novel control mechanism that opens new avenues of investigation into modulating cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the Ca 2+ binding proteins calmodulin (22) and centrin-2 (49) are required for mitosis, this work now provides the missing link that connects the cell biology of Ca 2+ signaling with mitosis in mammalian cells and has important implications for furthering our understanding of normal growth, development, and ageing. Because centrins-2 and -3 are centrosome-associated Ca 2+ binding proteins (50), this could be a clue as to why a centrosome-localized Ca 2+ signal is of crucial importance. Centrosomally localized Ca 2+ signaling is likely a universal phenomenon essential during mitosis and represents an entirely novel control mechanism that opens new avenues of investigation into modulating cell division.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because Sfr1 acts independently of centrin or because this role for centrin may have been undetectable in previous studies of centrin-null cells that display the full effects of centrin loss (21, 30, 31). Intriguingly, it has recently been shown that human Cetn3 can antagonize human Cetn2 function in centriole assembly, highlighting a role for Cetn3 in the inhibition of centrosome duplication (60). Depletion of Cetn3 in HeLa cells resulted in the overproduction of centrioles, providing an exciting potential parallel to our observed overproduction of basal bodies upon loss of the centrin-binding protein Sfr1.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there was marked variability in the percentage of cells with supernumerary centrioles, indicating that cancer cell lines possess distinct centriole numbers and levels of centrosome amplification. Interestingly, hPOC5 is capable of binding both human CETN2 and human CETN3, which have roles in promoting and antagonizing centrosome duplication, respectively (Sawant et al, 2015). Thus, depletion of CETN3 in HeLa cells results in a centriole overproduction, suggesting that centrins are important for modulating centriole number and this bidirectional contribution to centrosome duplication may be impaired in some human cancers.…”
Section: Discussionmentioning
confidence: 99%